Name Changes in Plants - Raizada, M. B. (Indian Forester, 1976)
Changes in plant names have caused considerable confusion among the Botanists, Foresters, Horticulturists, cultivators and others. As soon as a person gets used to a particular name or a set of names, he has to make an effort to try and get used to a completely different set. This article deals with the principles of the International Code of Botanical Nomenclature and describes how changes have brought about in the generic and specific names of different plants during the course of time. Examples of such changes have also been given in the paper.